An Analysis of Sentiment: Methods, Applications, and Challenges - Harish Dutt Sharma; Parul Goyal (Engineering Proceedings)
Sentiment analysis involves contextually examining text to identify and extract subjective information from source material. It aids businesses in comprehending the public sentiment surrounding their brand, product, or service while monitoring online discussions. Nevertheless, analyzing social media content is often limited to basic sentiment analysis and simple count-based metrics. Devices that allow the collection of huge amounts of unstructured, opinionated data are becoming increasingly connected with humans. Everyday-activity-related comments and evaluations have been obtained as a result of the advances in Internet-based services like social media platforms and blogs. This study supplies a comprehensive assessment of sentiment analysis approaches to provide academics with a global perspective on the analysis of feelings and its associated domain, applications, and challenges. To comprehend the applications of sentiment analysis, this article provides a detailed explanation of the technique for performing this activity. To comprehend the benefits and drawbacks of each method, they are then evaluated, compared, and discussed. To establish future perspectives, the difficulties of sentiment analysis are finally evaluated.